2017
DOI: 10.1112/plms.12007
|View full text |Cite
|
Sign up to set email alerts
|

Calabi–Yau caps, uniruled caps and symplectic fillings

Abstract: We introduce symplectic Calabi-Yau caps to obtain new obstructions to exact fillings. In particular, they imply that any exact filling of the standard contact structure on the unit cotangent bundle of a hyperbolic surface has vanishing first Chern class and has the same integral homology and intersection form as its disk cotangent bundle. This gives evidence to a conjecture that all of its exact fillings are diffeomorphic to the disk cotangent bundle. As a result, we also obtain the first infinite family of St… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 80 publications
2
21
0
Order By: Relevance
“…Moreover, we hope that our work maybe used towards settling Wendl's conjecture [22,Conjecture 9.23]: Any exact filling of (ST * Σ, ξ can ) is Liouville deformation equivalent to (DT * Σ, ω can ). This conjecture is true for g = 1 as shown by Wendl [21] and some evidence was obtained recently to verify this conjecture affirmatively by Li, Mak and Yasui [12] and also by Sivek and Van-Horn Morris [19], who showed that any exact filling must, at least topologically, bear some resemblance to DT * Σ for g ≥ 2.…”
Section: Introductionsupporting
confidence: 52%
“…Moreover, we hope that our work maybe used towards settling Wendl's conjecture [22,Conjecture 9.23]: Any exact filling of (ST * Σ, ξ can ) is Liouville deformation equivalent to (DT * Σ, ω can ). This conjecture is true for g = 1 as shown by Wendl [21] and some evidence was obtained recently to verify this conjecture affirmatively by Li, Mak and Yasui [12] and also by Sivek and Van-Horn Morris [19], who showed that any exact filling must, at least topologically, bear some resemblance to DT * Σ for g ≥ 2.…”
Section: Introductionsupporting
confidence: 52%
“…As illustrated by our examples, admitting a Calabi-Yau cap [24] does not impose finiteness on possible homology groups of Stein or minimal symplectic fillings of a contact 3-manifold. However, admitting a uniruled cap in the sense of [24] might be sufficient for this, which would extend the case of contact 3-manifolds with support genus zero we covered in Proposition 4.…”
Section: Remarkmentioning
confidence: 93%
“…(Note that this means that we can embed all our Stein fillings (X n , J n ) into K3 surface.) That is, the contact 3-manifold (Y, ξ) admits a Calabi-Yau cap, which by [24] implies that the Betti numbers of Stein fillings of (Y, ξ) is finite. In particular, it cannot admit arbitrarily large Stein fillings.…”
Section: Constructions Of Infinitely Many Fillingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Definition 5.5 ([13], [15]). Let (W, ω) be a concave symplectic 4-manifold with contact boundary (Y, ξ).…”
Section: Contact Aspectsmentioning
confidence: 99%